Zeranol induces COX-2 expression through TRPC-3 activation in the placental cells JEG-3. (September 2016) - Zhu, Yun; Yao, Xiaoqiang; Leung, Lai K.
Abstract: Transient Receptor Potential Channels (TRPs) are commonly expressed in the reproductive tissues in human. Many female reproductive processes have been associated with these TRPs. The mycotoxin zeranol or α-zearalanol is derived from fungi in the Fusarium family. Limited exposure to zeranol appears to be safe. In North America, farmers are using synthetic zeranol to promote growth in livestock. As the health risks of exposure to residual zeranol have not been determined, this practice is disallowed in the European Community. In the present study the cellular calcium levels were elevated in JEG-3 cells treated with zeranol at or above 10 nM. Subsequent study indicated that expressions of TRP channels were induced. In response to the calcium flow, ERK, P38 and PKCβ were activated and COX-2 expression was increased. Specific TRP inhibitors were employed to establish the connection between the ion channel activity and COX-2 expression, and TRPC-3 appeared to be the triggering mechanism. Since the involvement of COX-2 is implicated in placental development and parturition, exposure to this mycotoxin poses a potential threat to pregnant women. Highlights: Zeranol at > 10 nM increased calcium inflow and COX-2 in JEG-3 placental cells. TRPC-3 apparently was responsible for the induced COX-2 expression. PKC-β and/or P38 mediated the signal transmitted from TRP to the gene.